What’s used to gauge when engaging?: Determining academic librarian roles in research assessment reporting services - Miles, Rachel A.; Sutton, Sarah; Konkiel, Stacy (My University, 2016)
Abstract: Academic librarians play a key role in assisting faculty with assessing the impact of their research. In the rapidly changing environment of scholarly communication, librarians must stay abreast of emerging tools and metrics in order to effectively and reliably support and promote the research and creative activities at their institution. A recent survey administered to over 13,000 librarians at Carnegie-classified R1 institutions offers insight into the usage of research impact metrics and usage data among academic librarians when advising university faculty and when compiling evidence of research impact for faculty and administration. In particular, this poster examines the rates at which academic librarians are providing impact metric reporting services for faculty, departments, and administrators; the most popular tools used to prepare reports; and how disciplinary liaison responsibilities and job duties affect one’s likelihood to perform such services. Engaging with faculty and administration at the university is a crucial responsibility of academic librarians, and this poster presents a portrait of how academic librarians are leading the discussion in research impact.